Quality assessment of a daily diet for 1st grade in elementary school children in Bydgoszcz - Agnieszka Augustyniak; Maciej Świątkowski; Ewa Szymelfejnik; Monika Ameryk; Małgorzata Szamocka (Kazimierz Wielki University, 2016)
The aim of the dissertation was analysis and assessment of eating manner of 1st grade children from 5 elementary schools in Bydgoszcz. The analyzed group consisted of 85 students attending to 2012/2013 school year to 1st grade of 5 elementary schools in Bydgoszcz. Data concerning products, meals and beverages consumption were obtained for each person. The quality assessment of daily menus was carried out via two methods: the Bielińska's and Szczygłowa's method. The statistical analysis was performed at a significance level of p≤0.05. The assessment by Szczygłowa's method has shown 3% of appropriate menus and 17% of satisfactory menus. High percentage of unsatisfactory menus were stated (80%). Through Bielińska's method there were 37% of good menus, 48% required improvement and 15% were inappropriate. The analysis of particular Bielińska's assessment criteria has depicted that over 90% of menus contained, recommended for children, amount of 4-5 meals and proper breaks between meals. Unfortunately, less the half of menus contained vegetables/fruit in 3 meals, and only 20% - wholemeal bread, groats and pulses. Under 80% and 75% of menus contained properly raw vegetables/fruit at least once a day and minimum of 2 portions of diary products. The quality assessment has shown the differences in nutrition quality between sex groups and analyzed schools (≤0.05). Appropriate and satisfactory menus according to Szczygłowa almost 3 times more frequently appeared in boys' than girls' menus. 1. Quality assessment of menus among 1st grade in elementary school children in Bydgoszcz has indicated inaccuracies in their content. 2. Differences in quality between boys' and girls' menus and between analyzed schools have been stated. 3. Indicated inaccuracies in menus' content point out the risk of minerals and vitamins shortage in children' nutrition.